Role of tumor heterogeneity in drug resistance - Dhruv Kumar (Global Journal of Cancer Therapy - Peertechz Publications, 2017)
Cancer is a leading cause of death in men worldwide and the major cause of cancer related death is drug resistance [1,2]. In past few years, scientists have established tumor heterogeneity as a phenomenon of critical importance in the natural history of individual neoplasms and drug resistance [3-5]. The concept of tumor heterogeneity has a major impact on therapeutic approaches [6-9]. Drug resistance creates difficulty in cancer treatment and is directly linked to the tumor progression and poorer prognosis. As tumor heterogeneity is very common in almost all solid tumors, cancer therapy needs to become more personalized, selective, and specific [10-13]. Understanding the mechanisms of tumor heterogeneity and drug resistance will provide sustenance for the future development of personalized cancer medicine.